PROTOTYPE PENGONTROLAN TITIK FOKUS PANEL SURYA TERHADAP ENERGI MATAHARI SECARA OTOMATIS PADA STMIK Amik Riau - Rometdo - Muzawi; Ahmad - Fauzan; Lusiana - Lusiana (POLITEKNIK NEGERI BENGKALIS, 2018)
A solar panel is a device that can convert solar energy into electricity. The use of solar energy sources can be utilized as street lighting and garden lights. Today many use of solar panels mounted in static (silent) positions in one direction at one focal point will not get the maximum power point of the sun and sunlight received by the solar panel slightly so that it is inefficient at the time of charging the battery.The amount of solar energy that can be absorbed depends on the absorption of sunlight. Absorption can be optimized by making solar panels can continue to face the sun. This system uses ATMEGA8535 microcontroller with one temperature sensor to detect high solar thermal temperature received by solar panels and four photodiode sensors as a detection of light reflection received. These sensors can be able to provide a dynamic solar panels that are automatic and optimal in absorbing sunlight. With the absence of the use of solar panels as the lighting of the garden lights in Stmik Amik Riau and still using electrical energy from PLN, the purpose of this study is to build a solar panel control device that is able to follow the movement of the direction of the arrival of sunlight so it will be optimal in absorbing sunlight.Keywords - Solar Panel, microcontroller, Temperature Sensor, Photodiode Sensor.